Fossilization in adult second language acquisition - Han, Zhaohong, 1962- (Second language acquisition (Clevedon, England) ;, 2004)
This text is a systematic attempt to address the issue of fossilization in relation to a fundamental question in second language acquisition research, which is: why are learners, adults in particular, unable to develop the level of competence they have aspired to?